Optimization of clinical uricase production by Bacillus cereus under submerged fermentation, its purification and structure characterization - Khade S.M.; Srivastava S.K.; Kumar K.; Sharma K.; Goyal A.; Tripathi A.D. (My University, 2025)
The uricase production from Bacillus cereus after statistical optimization of process variables designed by L18 orthogonal array gave enhanced enzyme activity by 13% (29.7 U/mL) as compared with un-optimized medium (26.3 U/mL). The optimized process variables used for scale up of uricase production in a bioreactor gave 39.7 U/mL of uricase activity resulting 51% increase as compared with unoptimized medium. The Luedeking-Piret model classified the uricase production from Bacillus cereus as mixed-growth associated. The culture supernatant having uricase activity (7.7 U/mg) on purification by (NH4)2SO4 precipitation followed by anion-exchange and size-exclusion chromatography resulted 87 U/mg giving 11-fold purification. The purified uricase can be used for treating gout disease. The de novo amino acid sequence analysis of purified uricase by MALDI-TOF MS showed 301 amino acids and molecular mass of 34.4 kDa, which was corroborated by 35 kDa from SDS-PAGE. The phylogenetic tree generated by homologous amino acid sequences displayed the clustering of Bacillus uricase with fungal uricase. The secondary structure analysis of uricase by circular dichroism showed 18.6% α-helices and 27.4% β-strands. These results were corroborated by secondary structure prediction analysis by PsiPred. The homology modelling of uricase displayed the conserved T-fold structure. © 2018 Elsevier Ltd